TERRA EUROPAE - EARTHEN ARCHITECTURE IN EUROPE: A PROJECT FOR EARTHEN-ARCHITECTURE AWARENESS - Correia, Mariana; Carlos, Gilberto; Morot-Sir, Patrice; Chabenat, Marie; Vegas, Fernando; Mileto, Camila; Mecca, Saveiro; Dipasquale, Letizia; Guérin, René (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Traditional and contemporary earthen construction can be identiied in most European countries. The ecological and sustainable advantages associated with European earthen-building traditions make it a relevant material for construction nowadays. However, despite recent technology, earthen heritage remains fragile and threatened. This is why, this unique heritage and contemporary earthen architecture in Europe deserve to be further acknowledged and supported. In that aim, a European project was implemented in 2006-2007 making a state of the art of earthen architecture in Europe, particularly in France, Italy, Spain and Portugal. In order to complement these results at the scale of the European Union and to ensure a widest dissemination, the project ‘Terra InCognita – Earthen Architecture in Europe’ was launched from 2009 to 2011. The aims of this last research project were challenging: a scientiic publication gathering the contributions of authors from the 27 European Union countries; an updated European Atlas concerning traditional earthen techniques; a scientiic exposition and a photography exhibition, a European label, as well as a comprehensive website (www.culture-terra-incognita.org). The research project also initiated the launch of a Euorpean network during a symposium held in Marseleil (4-6 May 2011). This paper presents the results of the Terra InCognita project, as well as a relection concerning the relevancy of this kind of research initiatives, as they can contribute for the advancement of knowledge regarding earthen heritage, as well as the establishment of strategies to protect earthen heritage.